'Suddenly a stranger comes into the room': Interruptions in Brecht, Benjamin and Kafka. Issue 1 (2nd January 2016) - Rokem, Freddie
Abstract: This essay presents some suggestions for a re-examination of the notion of the interruption – a central device of Bertolt Brecht's epic theatre – as it has been reflected on and developed by Walter Benjamin. Franz Kafka is the connecting link, as Benjamin claimed that his world is a world of theater which can only be understood in terms of the gestus, a central notion in Brecht's epic theatre and of which the interruption is an example.